Role of sea ice as a biogeochemically active reservoir of iron and other trace metals - Duprat, LPADM (2021)
An increasing body of work has underlined the importance of Antarctic sea ice as a reservoir and source of iron (Fe) to the Southern Ocean, boosting local primary production and carbon export during spring and summer. The impact of Fe in controlling sea-ice and ocean productivity is unequivocal, but other trace metals (TMs) can also regulate productivity. Nevertheless, considerable uncertainty with respect to the pathways, fate and bioavailability of TMs in the sea-ice environment prevents us to accurately model the impact of predicted future changes in sea-ice extent and thickness on Southern Ocean ecosystems and our global climate. The aim of this PhD is to bring new evidence to our present understanding of the biogeochemical cycling of Fe and other bioactive TMs(Cd, Co, Cu, Mn, Ni and Zn) in Antarctic coastal land-fast (i.e. sea ice fastened to the coastline, ice shelves or to grounded icebergs) and pack ice (free drifting) and their relationship with regional primary productivity. The main findings from the analyses of TM distributions in sea ice from three field campaigns (SIPEX-2, 2012; Davis, 2015 and AAV2, 2016/17) along the East Antarctic coast are as follows: 1) Primary production in coastal land-fast ice is not Fe-limited during late-spring/early summer, potentially due to the high input of Fe from suspended sediment entrapped during ice formation; 2) Windblown dust from ice-free coastal landmasses can significantly contribute to the total Fe pool in land-fast ice and could become an important source of Fe and potentially other TMs, considering the projected expansion of ice-free areas across the Antarctic landmass by the end of the century; 3) Primary production in East Antarctic (fast and pack) ice is also not Fe-limited during mid-summer. Instead, low concentrations of inorganic nitrogen sources could be the main nutrient limiting sea-ice algal growth at this time of the year; 4) The formation of Fe-rich platelet ice underneath pack ice in proximity to glacial systems with negative ice mass balance ...